Integrating stormwater management and stream restoration strategies for greater water quality benefits. Issue 3 (18th March 2020) - Lammers, Roderick W.; Dell, Tyler A.; Bledsoe, Brian P.
Abstract: Urbanization alters the delivery of water and sediment to receiving streams, often leading to channel erosion and enlargement, which increases loading of sediment and nutrients, degrades habitat, and harms sensitive biota. Stormwater control measures (SCMs) are constructed in an attempt to mitigate some of these effects. In addition, stream restoration practices such as bank stabilization are increasingly promoted as a means of improving water quality by reducing downstream sediment and pollutant loading. Each unique combination of SCMs and stream restoration practices results in a novel hydrologic regime and set of geomorphic characteristics that interact to determine stream condition, but in practice, implementation is rarely coordinated due to funding and other constraints. In this study, we examine links between watershed‐scale implementation of SCMs and stream restoration in Big Dry Creek, a suburban watershed in the Front Range of northern Colorado. We combine continuous hydrologic model simulations of watershed‐scale response to SCM design scenarios with channel evolution modeling to examine interactions between stormwater management and stream restoration strategies for reducing loading of sediment and adsorbed phosphorus from channel erosion. Modeling results indicate that integrated design of SCMs and stream restoration interventions can result in synergistic reductions in pollutant loading. Not only do piecemeal and disunited approaches to stormwater management and stream restoration miss these synergistic benefits, they make restoration projects more prone to failure, wasting valuable resources for pollutant reduction. We conclude with a set of recommendations for integrated planning of SCMs and stream restoration to simultaneously achieve water quality and channel protection goals.